On the equivalence of McEliece's and Niederreiter's public-key cryptosystems - LI, Y. X. (Institutional Knowledge at Singapore Management University, 1994)
It is shown that McEliece's and Niederreiter's public-key cryptosystems are equivalent when set up for corresponding choices of parameters. A security analysis for the two systems based on this equivalence observation, is presented